Incidence of intestinal helminth and protozoan parasites in the department of Madre de Dios - Cornejo Donayre, Alberto (1959)
A survey on intestinal Protozoa and Helminth was carried out in Iberia and Puerto Maldonado, the most important populated centers in the Department of Madre de Dios; and also an exhaustive survey of health and sanitary conditions, and epidemiological factors which determins the high rates of infestation.